DnaK supports intracellular persistence of Staphylococcus xylosus and confers mechanical resilience to a human breast cancer cell line - Lei Ye; Guozheng Yu; Yi Cheng; Lijuan Fan (PLoS ONE, 2026)
Intratumoral Staphylococcus xylosus enhances the ability of breast cancer cells to survive mechanical shear stress, a critical barrier encountered during hematogenous metastasis. However, the bacterial determinants underlying this effect remain unclear. Here, we identify the bacterial molecular chaperone DnaK as a key factor enabling S. xylosus to promote shear-stress tolerance in a human breast cancer cell line. Deletion of dnaK did not affect bacterial adhesion to or invasion of MDA-MB-231 cells but significantly reduced sustained intracellular survival. Under oxidative and acidic stress conditions, the Δ dnaK mutant showed reduced survival compared with the wild-type strain, and its ability to enhance tumor-cell viability under shear stress was markedly impaired. Using a breast cancer–on–a–chip microfluidic model, we demonstrate that infection with wild-type or complemented Staphylococcus xylosus confers increased tumor-cell viability under laminar shear stress in a time-dependent manner, whereas cells infected with the Δ dnaK mutant fail to acquire shear-stress resistance and resemble uninfected controls. Together, these findings establish DnaK-dependent intracellular persistence of S. xylosus as a critical determinant of tumor-cell survival under mechanical stress, linking a conserved bacterial stress-response protein to cancer cell biomechanics in a metastasis-relevant context.